ASME 2008 Summer Bioengineering Conference, Parts a and B 2008
DOI: 10.1115/sbc2008-193149
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Nanoindentation Modulus and Mineral Density in Fracture Callus Tissues

Abstract: The stiffness and strength of a healing bone fracture depend on the geometry of the fracture callus as well as the mechanical properties of the callus tissues. In the clinical setting, the mechanical stability of a healing fracture is often estimated qualitatively based on the radioopacity of the callus tissue. However, a quantitative association between tissue mineralization and mechanical properties has yet to be established for these tissues. Quantifying callus tissue material properties and mineral content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The authors found a gradient of indentation modulus in the direction perpendicular to the implant surface, which gradually increases from 6.17 GPa at a distance lower than 150 ¡im up to 10.13 GPa at a distance of 1500 /xm from the implant surface. Interestingly, other groups have studied the temporal variation of bone biomechanical properties and mineral content of the external callus during bone healing [48][49][50][51], showing that the degree of mineralization of bone (DMB) is an important determinant of the microhardness and indentation modulus of bone tissue. The authors studied the biomechanical properties of newly formed bone tissue in a callus and found similar results since the bone apparent Young's modulus was lower than in newly fonned bone tissue and increases as a function of healing time.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a gradient of indentation modulus in the direction perpendicular to the implant surface, which gradually increases from 6.17 GPa at a distance lower than 150 ¡im up to 10.13 GPa at a distance of 1500 /xm from the implant surface. Interestingly, other groups have studied the temporal variation of bone biomechanical properties and mineral content of the external callus during bone healing [48][49][50][51], showing that the degree of mineralization of bone (DMB) is an important determinant of the microhardness and indentation modulus of bone tissue. The authors studied the biomechanical properties of newly formed bone tissue in a callus and found similar results since the bone apparent Young's modulus was lower than in newly fonned bone tissue and increases as a function of healing time.…”
Section: Discussionmentioning
confidence: 99%